GROUND TEMPERATURE REGIMES AND THEIR RELATION TO PERIGLACIAL PROCESSES IN THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - マツオカ, ノリカズ; モリワキ, キイチ; イワタ, シュウジ; ヒラカワ, カズオミ; MATSUOKA, Norikazu; MORIWAKI, Kiichi; IWATA, Shuji; HIRAKAWA, Kazuomi (National Institute of Polar Research, 1990)
P(論文) Rock and soil temperatures were observed on some nunataks in the Sor Rondane Mountains during 1985-1989. Three different types of automatic recorders made it possible to collect the temperature data at 1-to 4-h intervals throughout the year. Multiple freeze-thaw events were recorded on many bedrock surfaces and in soil surface layers during the summer season, whereas the ground was completely frozen during the remaining periods. The number of freeze-thaw cycles is comparable to those in mid-latitude alpine environments where the frost action, including frost weathering, heave and creep, is regarded as prevailing geomorphic process. Geomorphic change by the frost action, however, is believed to be insignificant in the most part of the Sør Rondane Mountains, because the water content of the ground is generally too low. The frost action may be effective only on the ground with a fairly high moisture content due to snow spray as well as with frequent freeze-thaw cycles. departmental bulletin paper